Development, Validity, and Reliability of the Women's Capabilities Index. Issue 3 (3rd July 2018) - Greco, Giulia; Skordis-Worrall, Jolene; Mills, Anne
Abstract: We report the results of a series of validity and reliability tests performed during the development of the Women's Capabilities Index (WCI) in Malawi. The WCI is a multidimensional measure based on Sen's capability framework for assessing women's quality of life. Construct validity was assessed by investigating the expected relationships of the dimensions with key socioeconomic characteristics. The majority of hypothesized associations were found to be statistically significant in the expected direction. This provides evidence that the index is measuring quality of life as intended in the conceptual model. Further evidence in support of the index's validity was given by the high degree of correlation between the WCI and another scale measuring comparable (but not identical) domains of quality of life. The results from the internal consistency and the test–retest repeatability also offered encouraging evidence on the reliability of the instrument. This is the first study to rigorously and comprehensively test for validity and reliability a capabilities index for a low-income setting. The results of the validity and reliability tests provide supportive evidence that a locally developed measure of capabilities can be used as a robust tool for the assessment of women's quality of life.